Bioaccumulation of polycyclic aromatic hydrocarbons in Panaceus merquensis and Calappa flammea in south sea water Jogjakarta - Lukitaningsih, Endang; Sudarmanto, B.S. Ari; Primadesa, Lina (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Polycyclic aromatic hydrocarbons (PAHs) are a class of organic chemicals, composed of fused benzene rings, occurred in the environment due to incomplete combustion of fossil fuels. Health concerns are focused on the metabolite transformation of PAHs, which is carcinogenic, mutagenic and terratogenic. Due to their hydrophobicity in aquatic environment, PAHs are accumulated to the more lipophilic ecocompartments such as biolipid tissues and sediments, so PAHs can be distributed through food chain system. In this research, five kinds of PAHs (i.e. pyrene, benz(a)anthracene, benz(k)fluoranthene, benz(a)pyrene and perylene) in shrimps (Panaceus merquensis) and crabs (Calappa flammea) collected from the south sea beach water system at Jogjakarta were investigated. PAHs analysis were worked out by gas chromatography with flame ionization detector. It can be shown from this research that PAHs accumulate into each biota.The results showed that bioacumulation factor value of total PAHs in shrimp and crab are 2388.33-23486.54 and 13870.92-96078 respectively. The logarithmic value of bioacumulation factor of total PAHs in shrimp and crab are 3.378-4.371 and 4.142-4.983 respectively. According to the World Health Organization (WHO) recommendation, the level of PAHs concentration in water sample is safe.Key words : polycyclic aromatic hydrocarbons, bioacumulation, shrimp (Panaceus merquensis) and crab (Calappa flammea)